Optimizing Science Process Skills through Multiple Representation - Arrofa, Acesta; Eli Hermawati; Adila Nurfadilah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This research is motivated by students' low science process skills in science subjects, which is caused by conventional teaching methods focusing on memorization, limited variations in learning models and minimal student involvement. This study aims to analyze the effect of the multiple representation learning model on improving science process skills in elementary school students. The method used in this research is the quantitative research method of experimental research type, using a nonquivalent control group design. The population used in this study were all fifth-grade elementary school students. The technique used in taking research samples is the Purposive Sampling technique. The sample in this study comprised students from the VA and VB classes, totalling 54. Data collection methods using test techniques and documentation. The instrument used in collecting data is a test question sheet. The data analysis technique used inferential statistical analysis. The results showed significant differences in science process skills between experimental and control classes and real disparities in improving skills that support the representation of multiple-representation learning models. So, the multiple representation learning model can improve science process skills in elementary school students. This research is expected to help improve the quality of science teaching and students' science skills in elementary schools.